Pyroshock Prediction of Ridge-Cut Explosive Bolts Using Hydrocodes. (20th September 2016) - Lee, Juho; Hwang, Dae-Hyun; Jang, Jae-Kyeong; Kim, Dong-Jin; Lee, YeungJo; Lee, Jung-Ryul; Han, Jae-Hung
Abstract : Pyrotechnic release devices such as explosive bolts are prevalent for many applications due to their merits: high reliability, high power-to-weight ratio, reasonable cost, and more. However, pyroshock generated by an explosive event can cause failures in electric components. Although pyroshock propagations are relatively well understood through many numerical and experimental studies, the prediction of pyroshock generation is still a very difficult problem. This study proposes a numerical method for predicting the pyroshock of a ridge-cut explosive bolt using a commercial hydrocode (ANSYS AUTODYN). A numerical model is established by integrating fluid-structure interaction and complex material models for high explosives and metals, including high explosive detonation, shock wave transmission and propagation, and stress wave propagation. To verify the proposed numerical scheme, pyroshock measurement experiments of the ridge-cut explosive bolts with two types of surrounding structures are performed using laser Doppler vibrometers (LDVs). The numerical analysis results provide accurate prediction in both the time (acceleration) and frequency domains (maximax shock response spectra). In maximax shock response spectra, the peaks due to vibration modes of the structures are observed in both the experimental and numerical results. The numerical analysis also helps to identify the pyroshock generation source and the propagation routes.